How a gene fuels ear infections - Sedigheh Delmaghani; Aziz El-Amraoui (eLife)
The DYRK1A enzyme is a pivotal contributor to frequent and severe episodes of otitis media in Down syndrome, positioning it as a promising target for therapeutic interventions.